Forging economic transformation: the role of agricultural research and productivity - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
A presentation by IITA Director General (Peter Hartmann) at the September Edition of NISER Research Seminar Series (NRSS)